Should High‐Frequency Hospital Users be Excluded from 30‐Day Readmission Quality Measures?. (20th August 2020) - Fouayzi, H.; Ash, A.
Abstract : Research Objective: To describe the characteristics of high‐frequency hospital users (with 4 or more hospital visits per year) and to assess the impact of their inclusion or exclusion on 30‐day hospital readmission. Study Design: We assigned MassHealth members to 17 accountable care organizations (ACOs) and 2 other groups (managed care organization or primary care clinician plan). We then compared demographics, morbidity burden, and social determinant of health factors for high‐frequency hospital users and low‐frequency users. We also evaluated the extent to which including or excluding hospitalizations of high‐frequency users from a 30‐day readmission measure changes its rate and variance. Population Studied: Managed care eligible MassHealth members between 18 and 64 of age with at least one acute hospitalization during 2016. Principal Findings: Of the 42, 794 eligible members, only 8.7% were high‐frequency hospital users, contributing 30.2% of all hospital visits. High‐frequency hospital users have many medical morbidities and significant psychiatric, substance abuse, and housing problems. Their readmission rate was 50.7% compared to 9.7% for other patients, and they contributed 72.0% of the total variance in 30‐day readmission. Conclusions: Despite their small numbers, high‐frequency hospital users exert a large influence on 30‐readmission rates. Implications for Policy or Practice: Thirty‐day readmission is being extended to ACOs as a quality measure. ACOs that disproportionately serve many high‐frequency hospital users may face unfair penalties for high readmission rates. Primary Funding Source: The study was funded by the State of Massachusetts.